MOTIVASI BELAJAR SISWA MATA PELAJARAN PAI MELALUI FILM KARTUN SYAMIL DAN DODO DI SD NEGERI 3 LAMPUYANG - Lisa Nurhikmah (CV. ADIBA ASIHA AMIRA, 2023)
Motivation to learn is the encouragement of students to achieve learning goals, for example understanding material or developing learning. So that to achieve student learning goals in the PAI subject at SD Negeri 3 Lampu, a cartoon film of Syamil and Dodo is needed which can foster understanding of the material for students. As in the material, let's carry out prayers, a cartoon film of Syamil and Dodo is needed, because in this material an explanation is needed that directly uses movement so that students are very easy to understand the material that has been conveyed. This study aims to describe student learning motivation after using the cartoon film Syamil and Dodo on the PAI subject at SD Negeri 3 Lampuyang, describe student responses to the cartoon film Syamil and Dodo, and describe the barriers for students and teachers to understand the messages in the Syamil cartoon film. and Dodo. As for the subjects in this study were PAI subject teachers and 15 fourth grade students at SD Negeri 3 Lampuyang. This research uses a descriptive qualitative approach. Data collection was carried out by observation, interviews and documentation. The validity of the data was done by using triangulation techniques and triangulation of sources. This research uses a descriptive qualitative approach. Data collection was carried out by observation, interviews and documentation. The validity of the data was done by using triangulation techniques and triangulation of sources. Data analysis was carried out by inductive method. Therefore, the results show that (1) After watching the cartoon film Syamil and Dodo, students are motivated to learn the material, let's pray, among them the students look very enthusiastic about learning, are curious about what the teacher will teach, pay attention to what displayed by the teacher, and students look enthusiastic about doing the assignments given by the teacher.(2) The students' response to the cartoon film Syamil and Dodo was very good, because it made it easier for them to understand the lesson. During the lesson the students listened carefully to the cartoon film Shamil and Dodo. The material let's pray. (3) There are almost no barriers between students and teachers in understanding the messages in the cartoon film Syamil and Dodo, because the messages conveyed are very clear and easily understood by both teachers and students. The only obstacle was felt by the teacher when broadcasting, sometimes the electricity went out, so that the showing of the cartoon film Syamil and Dodo was delayed.